A Protocol for Minimalist Curriculum Mapping - Agahi, Sama; Salwén, Håkan (Teaching and Learning Inquiry, 2025)
Curriculum mapping is a powerful tool that teachers and pedagogical developers can use to improve courses. It can, however, be both costly and time-consuming. This article describes a protocol for minimalist curriculum mapping that is easy to implement, highly flexible, and requires no specialized software. The described method is paired with the use of supplemental instruction, allowing access to high-quality information without the need to conduct interviews or distribute questionnaires. In the case described, minimalist curriculum mapping was used to determine the optimal use of digital tools for online courses. The protocol described can easily be adapted to serve other purposes. It can also be used without reliance on supplemental instruction. It is argued that this makes the protocol a simple and flexible way to reap some of the benefits of curriculum mapping without incurring all of the costs.